Analysis of interface interaction of aggregate-asphalt system and its effect on shear-slip behavior of asphalt mixture. (20th December 2020) - Su, Jinfei; Li, Peilong; Wei, Xiaofeng; Sun, Shengfei; Zhu, Lei; Dong, Chao
Highlights: Two composite indexes are proposed to analyze the interface interaction. The influence of interface interaction on the shear-slip behavior were analyzed. The interaction parameters except for AC-13L exhibit a good correlation with τ sl . Abstract: The interface interaction of aggregate-asphalt system is a key factor affecting the strength formation and deterioration of the asphalt mixture, which has a great influence on the distress and durability of pavement. To analyze the influence of the interface interaction of aggregate-asphalt system on the shear-slip behavior of asphalt mixture, two self-developed testers were adopted to measure the parameters of particle contact and interface shear-slip, and the effective evaluation methods were proposed on the mesoscopic level. The results indicate that the interface interaction is from the coupling effect of the particle contact and the bonding and lubrication of asphalt. Among involved aggregate-asphalt systems, the AC-13L system has a strong contact strength, while its skeleton structure is easily affected by the lubrication of asphalt. The contact and interaction parameters of involved aggregate-asphalt systems except for AC-13L exhibit a good linear correlation with the shear-slip parameters of asphalt mixtures. The AC-20M system has the strongest contact effect and easily forms a multilevel dense interlocking structure interacting with asphalt, which shows the best resistance to shear-slip deformation. The interference of fine aggregates and the lubrication of asphalt can adversely affect the resistance to slip deformation of asphalt mixtures.